Motion encoding in language and space - Dimitrova-Vulchanova, Mila.; Zee, Emile van der. (Oxford : Oxford University Press, 2013)
This text brings together researchers in linguistics, computer science, psychology and cognitive science to investigate how motion is encoded in language. Part I considers the parameters of the field, while part II looks at the way in which spatial scale or granularity plays a role in the encoding of motion in language.
Series from CIP print record.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Motion in language; Computational linguistics